FORMULATION AND IN-VITRO EVALUATION OF MOUTH DISSOLVING TABLETS OF AMLODIPINE AND ROSUVASTATIN - Begum, Shireen; Azeez Basha, Syed Abdul; Fatima, Shazia (International Journal of Current Pharmaceutical Research, 2015)
Objective: Mouth Dissolving Tablets (MDT) are most accepted and exploited for the drug delivery for the patients who are having difficulty with swallowing i.e., mainly pediatric's and Geriatric's. Amlodipine besylate (ADB) is an anti-hypertensive and it is also used in many Coronary artery diseases, Whereas Rosuvastatin Calcium (RSC) is an anti-hyperlipidemia that prevents of Atheroma. In the present study a combination of ADB, RSC is formulated into a mouth dissolving tablet using three super disintegrants such as Croscarmellose Sodium (CCS), Cross povidone (CP), Sodium Starch Glycolate (SSG) at various concentrations to enhance the disintegration and dissolution of ADB, RSC to improve bioavailability of the drugs Methods: The tablets were prepared by using direct compression method and evaluated for weight variations, Hardness, Friability, Wetting time, disintegration time (DT) and Dissolution study. Prepared tablets are subject to FT-IR Study for Characterization and compatibility study. Results: No Chemical interaction between drug and excipients were indicated in the FT-IR. Disintegration and dissolution profiles decreases with addition of super disintegrating agents like Croscarmellose Sodium (CCS), Cross povidone (CP), Sodium Starch Glycolate (SSG). Conclusion: Among all the formulation F12 with CP in 5% and SSG 5% Concentration found to be best in drug release profile.